A model for entropy generation in stagnation‐point flow of non‐Newtonian Jeffrey, Maxwell, and Oldroyd‐B nanofluids. Issue 1 (17th October 2018) - Almakki, Mohamed; Nandy, Samir Kumar; Mondal, Sabyasachi; Sibanda, Precious; Sibanda, Dora
Abstract: We present a generalized model to describe the flow of three non‐Newtonian nanofluids, namely, Jeffrey, Maxwell, and Oldroyd‐B nanofluids. Using this model, we study entropy generation and heat transfer in laminar nanofluid boundary‐layer stagnation‐point flow. The flow is subject to an external magnetic field. The conventional energy equation is modified by the incorporation of nanoparticle Brownian motion and thermophoresis effects. A hydrodynamic slip velocity is used in the initial condition as a component of the stretching velocity. The system of nonlinear equations is solved numerically using three different methods, a spectral relaxation method, spectral quasilinearization method, and the spectral local linearization method, first to determine the most accurate of these methods, and second as a measure to validate the numerical simulations. The residual errors for each method are presented. The numerical results show that the spectral relaxation method is the most accurate of the three methods, and this method is used subsequently to solve the transport equations and thus to determine the empirical impact of the physical parameters on the fluid properties and entropy generation.